Criticism and analysis of the machine translation of news websites from Persian into Arabic - AbdulAbbas, Omar Amin (Al-Adab Journal, 2021)
It is natural that after global convergence and the exchange of information and communication, the demand to translate ideas from one language to another will be greater and unprecedented, especially with regard to the work of international companies and governments, due to the essential role of translation. We have learned about events in human history that led to an incorrect translation severing relations between countries, and in this case; The translation was not just a process of translating words, but rather transformed into a change in meaning and intent.In recent years, the importance of machine translation has increased and its role expanded with the development of communication tools, as various institutions have realized the importance of communicating with people around the world through this type of translation, including international news sites.International news sites, including Farsi-speaking, included automatic translation services from Persian to Arabic in their news, and despite the development of this type of translation, it was not without errors that required identifying and criticizing it in terms of translational criticism.Given the increasing importance of translation criticism in the field of Persian and Arabic studies and the lack of topics that address this issue in study and application, we have assumed the responsibility of criticizing the automatic translation of news in Persian news sites according to specific criteria.Therefore, in our research, we selected models of machine-translated news whose translation does not match the original text, and we performed translation criticism with analysis on them.